2017
DOI: 10.3847/2041-8213/aa9057
|View full text |Cite
|
Sign up to set email alerts
|

The Electromagnetic Counterpart of the Binary Neutron Star Merger LIGO/Virgo GW170817. V. Rising X-Ray Emission from an Off-axis Jet

Abstract: We report the discovery of rising X-ray emission from the binary neutron star (BNS) merger event GW170817. This is the first detection of X-ray emission from a gravitational-wave source. Observations acquired with the Chandra X-ray Observatory (CXO) at t ≈ 2.3 days post merger reveal no significant emission, with L x 3.2 × 10 38 erg s −1 (isotropic-equivalent). Continued monitoring revealed the presence of an X-ray source that brightened with time, reaching L x ≈ 9 × 10 39 erg s −1 at ≈ 15.1 days post merger. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
390
1
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(427 citation statements)
references
References 53 publications
31
390
1
5
Order By: Relevance
“…We first note that the light curves are not well described by a power law, indicating minimal contribution from a GRB optical afterglow over the timescale of our observations. This is consistent with modeling of the afterglow based on X-ray and radio observations (Margutti et al 2017;Alexander et al 2017).…”
Section: Light Curvessupporting
confidence: 73%
“…We first note that the light curves are not well described by a power law, indicating minimal contribution from a GRB optical afterglow over the timescale of our observations. This is consistent with modeling of the afterglow based on X-ray and radio observations (Margutti et al 2017;Alexander et al 2017).…”
Section: Light Curvessupporting
confidence: 73%
“…The properties of the wide-jet model are consistent with Alexander et al (2017b), Granot et al (2017), Margutti et al (2017), and Troja et al (2017b). However, the two distinct models, discussed in this Letter, show that there is significant degeneracy between the afterglow parameters (for a more detailed study of the afterglow parameter space, see Granot et al 2017).…”
Section: Modeling the Broadband Afterglowsupporting
confidence: 73%
“…This behavior is inconsistent with known X-ray afterglows. When the X-ray afterglow was detected with Chandra (Haggard et al 2017b;Margutti et al 2017;Troja et al 2017b), the luminosity of~- was still 2.6 dex fainter than that of any GRB with detected X-ray afterglow. This faintness of the afterglow is also reflected in the very low energy release at γ-rays, g E ,iso .…”
Section: Grb 170817a In the Context Of Other Sgrbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent observations with Chandra revealed that the X-ray afterglow continued to increase unexpectedly until ∼110days post merger (Margutti et al 2017;Troja et al 2017;Ruan et al 2018). Ruan et al (2018) further found that the radio emission brightened at approximately the same rate as that of the X-ray emission, which indicates that they share a common origin (see also Mooley et al 2018).…”
Section: Introductionmentioning
confidence: 99%